2020
DOI: 10.1038/s41598-020-76499-z
|View full text |Cite
|
Sign up to set email alerts
|

Different experimental multiple trauma models induce comparable inflammation and organ injury

Abstract: Multiple injuries appear to be a decisive factor for experimental polytrauma. Therefore, our aim was to compare the inflammatory response and organ damage of five different monotrauma with three multiple trauma models. For this, mice were randomly assigned to 10 groups: Healthy control (Ctrl), Sham, hemorrhagic shock (HS), thoracic trauma (TxT), osteotomy with external fixation (Fx), bilateral soft tissue trauma (bsTT) or laparotomy (Lap); polytrauma I (PT I, TxT + HS + Fx), PT II (TxT + HS + Fx + Lap) and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
8
0
4
Order By: Relevance
“…Prior studies have shown that severe trauma causes damage to trauma-remote organs such as lungs or liver, mainly by an uncontrolled systemic and local proinflammatory response ( 4 6 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that severe trauma causes damage to trauma-remote organs such as lungs or liver, mainly by an uncontrolled systemic and local proinflammatory response ( 4 6 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Femur fracture in particular can induce remote organ complications, especially in the lungs ( 4 ). Lung and remote lung injury (RLI), a common complication after surgical procedures post-trauma, have also been shown in the combinatory model of femur fracture accompanied by hemorrhage (THFx) in mice ( 5 , 6 ). Many inflammatory pathways and mediators including cytokines and other damage-associated molecular patterns were found to be important triggers for the development of lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Травма є однією з провідних причин смерті в усіх вікових групах у всьому світі. Незважаючи на значні вдосконалення хірургічних стратегій, а також інтенсивної терапії пацієнтів із політравмами, показники смертності та інвалідності все ще залишаються високими [7,11]. Підвищений рівень алкоголю в крові пов'язаний майже з усіма видами та механізмами травм, включаючи падіння, аварії на велосипеді, автотранспортні аварії, травми голови [8].…”
Section: вступunclassified
“…Overwhelming systemic inflammatory reactions, both polytrauma-triggered and/or microbial triggered, contribute to an adverse outcome not only physiologically but also lowering the operative success, especially in the field of trauma [ 1 , 2 ]. The damage control concept in the treatment of polytrauma patients takes account to avoid infectious and inflammatory complications but cannot be monitored in any way.…”
Section: Introductionmentioning
confidence: 99%